STRENGTHENING CHARACTER EDUCATION IN FACING SOCIAL DISRUPTION AND DEHUMANIZATION OF SOCIETY 5.0 - lala intan gemala (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This paper discusses the importance of character education for students in dealing with social disruption and dehumanization of society 5.0 . Around the 2010s the idea of the industrial revolution 4.0 was launched with intellectual engineering (artificia intelligence) and the internet of things as the main foothold for the connectivity of human life with machines. The main principle in this revolution is that it is easy, cheap, fast and accessible anywhere (simple, cheaper, faster and accessible). Therefore, the industrial revolution 4.0 is understood as a new civilization that will present opportunities for success as well as challenges for humans and their lives, especially the younger generation (millennials). ) as an agent of social change and a milestone in the history of his life. Digitization of information has provided very wide and even unlimited opportunities for every human being to access information and communicate and interact quickly and easily at a very low cost, so that slowly the industrial revolution 4.0 has fundamentally caused changes in mindset and behavior even identity as a human.